ANALISIS KRITIK SOSIAL DALAM CERPEN “TIGA KUBURAN LAIN” KARYA T AGUS KHAIDIR - Yuli Sartika Ginting; Siti Zahara; Kartika Nadila Putri; Nur Amelia (Universitas Nias Raya, 2025)
This study aims (1) to describe the social conditions of society depicted in the short story “Tiga Kuburan Lain” and (2) to identify and analyze the forms of social criticism that emerge within it. The research employs Soekanto’s social theories as an analytical foundation to understand the societal dynamics presented in the literary text. The research method used is a qualitative descriptive approach, as it is suitable for examining meanings, messages, and social phenomena represented narratively. The data source of this study is the short story “Tiga Kuburan Lain” by T. Agus Khaidir, published on Kompas.com in the October 2024 edition. Data collection techniques include close reading and note-taking, conducted by carefully examining the text and recording segments relevant to the research focus. Based on the findings, several portrayals of social conditions within the story are identified, including: (a) shifts in the attitudes and mindsets of the older generation from previously held values, (b) the presence of discrimination against minority groups as reflected through unjust social treatment, (c) the diminishing spirit of communal cooperation (gotong royong), once a hallmark of the community, and (d) the indecisiveness of political figures in addressing the issues presented in the narrative. Furthermore, the forms of social criticism found in the short story include criticism of political practices, criticism of discriminatory behavior, and criticism of sociocultural changes within society. Thus, the short story not only presents a narrative but also conveys a critical reflection on social realities.